Diseño, construcción y desarrollo de guías prácticas con DYOR - Chávez Retete, Jorge Miguel (2022)
The following project has been based on the application of educational robotics as a learning mechanism through a DYOR robot, which allows students to motivate themselves to develop their intellectual capacity efficiently. To define the work process, a constant bibliographic search was carried out in order to understand the importance of motivation in the learning process. It also describes the programming language in Arduino to be executed in a robot called DYOR, which is a robot designed by myself, and also to know the components that will be part of the robot and give movement to it. Furthermore, to develope practical guidelines for the design and construction as well as some programming that the robot will have. Once the practical guidelines were established, as well as the relevant programming, a small course was developed and addressed to the first cycle students of the electrical engineering college of the National University of Loja, where a small programming course was taught about Arduino language. Additionally, exercises were developed by the students, who first learned to turn on a Led light, and eventually to program a DYOR robot. The methodology applied to validate the practical guides was carried out by surveying students, who answered a questionnaire, where specific questions about programming language, DYOR robot and educational robotics were established, the survey helped collect information about the thoughts of the students regarding the programming course and the ability to acquire knowledge of topics exposed in an interesting way, which motivates them to learn and learn in an innovative way. Keywords: practical guides whit DYOR, programming language, robots design, Arduino, learning to program.